INFLUENCE OF BELA 0PHIOLITE ON TRACE ELEMENT COMPOSITION OF JURASSIC AND CRETACEOUS CARBONATE ROCKS OF PHUARI AREA BALOCHISTAN - Uddin, Saleem; Naseem, Shahid; Sheikh, Shamim Ahmed; Siddique, Seema Naz (Biological Sciences - PJSIR, 2002)
Major and selected trace element analyses of carbonate rocks of LoraJai formation and Parh limestone from Ph uari area of Balochistan province were carried out. These carbonates are melanged with rocks of Bela Ophiolite. The distribution of variou s trace elements (Ni, Cr, Cu, Mn, Cd, Pb and Zn) in the carbonate rocks in the light of their plots was discussed with respect to primary dispersion , mobility and physicochemical environment. An attem pt has also been made to evaluate the influence of magmatic bodie s for im pregnating trace elements into limestones. High Ni, Cr, Mn, Cu, Cd, Pb and Zn assemblage show similarity with tholeitic Mid Oceanic Ridge Basalt (MORB). Petrographic studies were also made for descri ption and classification of carbonates. Presence of dark glassy/amorphous igneous material in thin-sections empha sizes the influence of igneous bodies on carbonate rocks.